A Political Economy of the Immigrant Assimilation: Internal Dynamics - Gil Epstein; Ira Gang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Within immigrant society different groups wish to help the migrants in different ways - immigrant societies are multi-layered and multi-dimensional. We examine the situation where there exists a foundation that has resources and that wishes to help the migrants. To do so they need migrant groups to invest effort in helping their country-folk. Migrant groups compete against one another by helping their country-folk and to win grants from the foundation. We develop a model that considers how such a competition affects the resources invested by the groups' supporters and how beneficial it is to immigrants. We consider two alternative rewards systems for supporters - absolute and relative ranking - in achieving their goals.
Keywords: 330